Stress Analysis and Structural Optimization of Steel–Concrete Joint of Zhonghua Road Bridge in Liaocheng - Jie Jin; Junlin Zhang; Ye Li; Zengkui Xie; Lipo Yang (Advances in Civil Engineering)
Based on Zhonghua Road Bridge in Liaocheng city, a single tower hybrid cable-stayed bridge, the stress of the steelconcrete joint of the girder is studied using the finite element method with the software MIDAS and ANSYS. The beam element model of the whole bridge is established in MIDAS CIVIL, from which the internal forces of the critical sections of the steel–concrete joint under six adverse conditions are obtained. Then, the results are applied in the refined solid-shell finite element model established in ANSYS. With the stress analysis, it is found that when the steel–concrete joint is used in the girder of the single tower cable-stayed bridge, both the compressive strength of concrete and the tensile strength of steel can be fully used, and the structural stiffness can be smoothly transferred through the two different materials in the joint, which makes the structural behavior more reasonable. The detailed stress analysis also shows that it is prone to generate considerable stress concentration at the corners and the connection between the steel lattice chamber and the pressure bearing plate, and the concentration can be avoided by local stiffening and smoothing of the chamfers. The sensitivity analysis of the web thickness in the joints and bearing plates showed that increasing the thickness of the intermediate web would lead to a moderate reduction in the stress of the web itself, while the stress in the steel member remained relatively constant. However, when the thickness of the bearing plate is increased from 60 to 80 mm, the stress of each part of the steel plate in the steel grid will be significantly reduced, and the maximum reduction can reach 48%. The improvement of concrete strength has little effect on the stress of the steel cell, and the C50 concrete strength grade used in the design is more reasonable.